MULTIAGENT METHODS OF MANAGED DISTRIBUTED COMPUTING - Барабаш, Олег; Колумбет, Вадим (SWorldJournal, 2021)
The article considers a multi-agent system that provides an integration approach to computational management for a cluster Grid system of computational type, the nodes of which have a complex hybrid structure.